Influence of Cash Holdings and Capital Structure on Financial Performance in Listed Real Estate Firms - Duc Tai Do; Van Luyen Le; Thi Ngoc Huyen Vu (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2023)
This study aims to evaluate the impact of cash holdings and capital structure on the financial performance of listed real estate firms in the Hochiminh Stock Exchange (HSX). Financial performance is measured by return on equity (ROE). Cash holdings are measured by cash and cash equivalents divided by total assets. Capital structure is measured by debt-to-equity ratio. The study uses balanced panel data from 25 real estate firms from 2017 to 2022 with 149 observations and OLS regression methods. The results show a positive linear effect between the cash holdings ratio and the return on equity, while the capital structure does not impact the financial performance. From the research results, the authors also make recommendations to optimize financial performance, and solutions to choose the optimal capital structure and optimal cash holding of the real estate firms.